Effect of interstitial Li + ion and vacant site Li + ion on the properties of novel Li 2.05 ZnAl 0.05 Si 0.95 O 4 and Li 1.95 Zn 0.95 Cr 0.05 SiO 4 ceramic electrolytes - Adnan, S.B.R.S.; Salleh, F.M.; Mohamed, N.S. (Elsevier, 2016)
Lisicon-typeceramic electrolytes, Li2.05ZnAl0.05Si0.95O4 (interstitial Li-ion) and Li1.95Zn0.95Cr0.05SiO4 (Li-ion vacant site) were synthesized by sol gel method. X-ray diffraction was applied to investigate the phase, structure and unit cell parameters of both solid electrolytes. Complex impedance spectroscopy was carried out in the 10 Hz–10 MHzfrequency range and temperature range from 303–773 K to study the electrical properties of the electrolytes. Both compounds were indexed to the monoclinic unit cell in the space group P21/m. Li2.05ZnAl0.05Si0.95O4 compound gave slightly higher total conductivity values of 3.39×10−5 S cm−1 at ambient temperature and 1.03×10−4 S cm−1 at 773 K compared to Li1.95Zn0.95Cr0.05SiO4 which showed total conductivity values of 4.17×10−6 S cm−1 at ambient temperature and 4.01×10−5 S cm−1 at 773 K. It’s evident that, the Li2.05ZnAl0.05Si0.95O4 yielded a compound containing a greater number of ions with higher mobility compared to the Li1.95Zn0.95Cr0.05SiO4 compound. Linear sweep voltammetry results demonstrated that the Li1.95Zn0.95Cr0.05SiO4 and Li2.05ZnAl0.05Si0.95O4 ceramic electrolytes were electrochemically stable up to 2.7 V versus a Li/Li+.